Peri Perabun Remalan Bertungket: Communication Values Based on Local Wisdom of Gayo Culture - Irwansyah; Mesiono; Asnil Aida Ritonga (JTP - Jurnal Teknologi Pendidikan, 2026)
This study aims to explore the philosophical and historical meaning behind the expression "peri perabun remalan bertungket" and to understand how these values once played a role in maintaining social harmony. This research was conducted in the form of an ethnographic study, by collecting the knowledge of traditional elders and analyzing historical and cultural literature. Data collection used interview, observation, and documentation techniques. This study uses a qualitative flow model analysis by following three stages, namely data reduction, data display, and drawing conclusions. The results of this study reveal that the community’s understanding from the adult generation comprehends the words, meaning, and actions regarding peri perabun remalan bertungket in Gayo community communication, whereas among the younger generation, they understand the meaning of peri perabun remalan bertungket, although the phrase is not verbally expressed. Modernization and globalization influence the shifting of customary values such as peri perabun remalan bertungket. Internal influences change the mindset of the younger generation, including the lack of inheritance of oral culture. Meanwhile, the external influences include modern communication technology, globalized popular culture lifestyles, and the dominance of national and foreign languages. Through this effort, it is hoped that the value of "peri perabun remalan bertungket" can once again become part of communication culture that brings harmony and respect in the present era.